Theory and applications of long-range dependence - Doukhan Paul; Oppenheim George; Taqqu Murad S (Boston Birkhauser, 2001)
Devoted to applications in the areas of simulation, estimation and wavelet techniques, traffic in computer networks, econometry and finance, multifractal models, and hydrology. Diagrams and illustrations will enhance the presentation.
Keywords: Brownian motion processes; Time-series analysis